RNA analysis of intronic variants in the LAMA2 gene detected by whole genome sequencing confirms a rare dual diagnosis of incontinentia pigmenti with limb‐girdle muscular dystrophy. Issue 4 (7th April 2023) - Washington, Camerun; Stolerman, Elliot S.; Cooley‐Coleman, Jessica A.; Jones, Julie R.; Chen‐Deutsch, Xiangwen
Abstract: We see that a multiple methods approach to diagnosis remains necessary in the era of whole genome sequencing. We also observe that reproductive risk genetic counseling can be a motivating factor for further testing along the diagnostic odyssey.